Double shear tests of high-strength steel bolted connections with reduced tightening. (1st April 2022) - Zhang, Xiaoyong; Lin, Xiang; Sun, Linhao; Lei, Yongchun; Chen, Jincheng; Lin, Hengzhou; Chen, Yu
Abstract: This paper presents a study on shear resistance of high-strength steel bolted connections with reduced tightening. The double shear test was conducted with 108 specimens of high-strength steel bolted connections, including 96 steel bolted connections with different torque reduction percentages and 12 steel bolted connections under standard torque as a control group. The main variables of the test include the percentage reduction of tightening torque, steel bolt type, high-strength steel bolt grade and steel plate surface treatment. The effects of four parameters on the failure mode, strain distribution, slip resistance, shear capacity, initial stiffness and ductility of high-strength steel bolted connections under loading are studied. The test results indicate that the slip resistance and the shear capacity of the specimens are decreased with decreasing of tightening torque degraded rapidly. In the bolt loading stage, the stiffness of the steel bolted connections is decreased with the reduction of tightening torque, and decreasing rate of the stiffness is increased with the decrease of tightening torque. Nevertheless, the ductility of the steel bolted connections is increased with the reduction of the tightening torque. Among these effects of the four variables, the degree of reduction of the tightening torque has the greatest effect on the shear capacity of the specimen. The strength grade of high-strength steel bolts and the surface treatment method have the second effect on the shear capacity. In addition, the calculated formula of ultimate capacity was provided in this study. The calculated results were in good agreement with the test result. Furthermore, the finite element model was provided to simulate and analyze the shear behavior of high-strength steel bolted connection with reduced tightening. Highlights: The shear behavior of high-strength steel bolted connections with less-tighten is investigated. The degree of reduction of the tightening torque has the greatest influence on the shear behavior of the specimen. The calculated formula can be used to accurately calculate the ultimate shear capacity. The finite element model is presented and verified by the experimental data.